Dissolved inorganic carbon enhanced growth, nutrient uptake, and lipid accumulation in wastewater grown microalgal biofilms. (March 2015) - Kesaano, Maureen; Gardner, Robert D.; Moll, Karen; Lauchnor, Ellen; Gerlach, Robin; Peyton, Brent M.; Sims, Ronald C.
Highlights: Bicarbonate added to enhance algal biofilm growth and nutrient uptake. Bicarbonate added to trigger lipid production in nitrogen stressed algal biofilms. Nutrient removal influenced by growth phase of algal biofilms. Bicarbonate addition enhanced photosynthesis in algal biofilms. Abstract: Microalgal biofilms grown to evaluate potential nutrient removal options for wastewaters and feedstock for biofuels production were studied to determine the influence of bicarbonate amendment on their growth, nutrient uptake capacity, and lipid accumulation after nitrogen starvation. No significant differences in growth rates, nutrient removal, or lipid accumulation were observed in the algal biofilms with or without bicarbonate amendment. The biofilms possibly did not experience carbon-limited conditions because of the large reservoir of dissolved inorganic carbon in the medium. However, an increase in photosynthetic rates was observed in algal biofilms amended with bicarbonate. The influence of bicarbonate on photosynthetic and respiration rates was especially noticeable in biofilms that experienced nitrogen stress. Medium nitrogen depletion was not a suitable stimulant for lipid production in the algal biofilms and as such, focus should be directed toward optimizing growth and biomass productivities to compensate for the low lipid yields and increase nutrient uptake.